Dysregulated expression of circular RNAs serve as diagnostic and prognostic markers in ovarian and cervical cancer: A PRISMA-compliant systematic review and meta-analysis. Issue 39 (1st October 2021) - Liu, Fengyuan; Wu, Xinrui; Zhu, Huixia; Wang, Feng
Abstract: Introduction: Recent studies have reported a connection between non-coding RNAs such as circular RNAs (circRNAs) and the prognosis of various cancers. However, the mechanism of circRNA in ovarian cancer and cervical cancer has not been consistent. We evaluated the diagnostic and prognostic roles of circRNAs in ovarian and cervical cancer by meta-analysis. Methods: Pooled hazard ratios with 95% confidence intervals were to estimate overall survival. Diagnostic efficacy was estimated by sensitivity, specificity and area under curve. Results: By searching PubMed, Embase, the Web of Science databases, and other sources, we obtained a total of 22 studies with 2059 patients from Asia population. High expression levels of oncogenic circRNAs were significantly associated with poor prognoses both in ovarian and cervical cancer. However, elevated expression levels of tumor-suppressor circRNAs were linked with favorable survival time in ovarian cancer. As for diagnostic role, the area under the curve value in ovarian cancer and cervical cancer is 0.89 and 0.93, respectively. Conclusions: CircRNAs have the prospect of becoming a promising biomarker for diagnosis and prognosis of ovarian and cervical cancer. Accordingly, circRNAs might be novel indicators and targets of therapy for ovarian and cervical cancer. Abstract : Supplemental Digital Content is available in the text